Digitally Programmable Active-R Function Generator - Muhammad Taher Abuelma'Atti (Active and Passive Electronic Components)
A new digitally programmable active-R function generator circuit is presented. The circuit uses four operational amplifiers, two operational transconductance amplifiers, and resistors. The circuit can provide sinusoidal, square, and triangular waves with digitally programmable frequency. The frequency is linearly proportional With the digital input.